Analisis Semiotika Unsur-Unsur Budaya Jawa Timur Dalam Film Bumi Manusia - Inda Febriani Ali; Minarni Tolapa; Salma P. Nua (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2022)
This study aims to analyze the cultural signs of East Java used in the film Bumi Manusia. The method used in this study is a qualitative method that will produce descriptive data that will explain how the meaning of East Javanese culture is contained in the film Bumi Manusia. The subject of this research is a file of the Earth of Man with a duration of 181 minutes, which then selects the pieces, then 7 scenes are obtained as objects that are not East Javanese culture which is analyzed based on Roland Barthes' semiotic theory to reveal the denotation, connotation, and myths of the elements. culture used in the film Earth of Man. The results of this study are cultural signs used in the film Bumi Manusia which have meaning, lessons, and life guidelines from the philosophy behind every cultural ritual that is undertaken. How to respect parents, also the actions of women and men in everyday life, and in married life that can be taken as examples to be applied in everyday life.